Study of cubic III-V nitrides for device applications - Zainal, Norzaini Binti (2010)
This thesis describes the optimisation of the growth of bulk cubic GaN with low hexagonal content and with the intention of making it a commercial substrate for device applications. The optimised material was then applied for fabrication of cubic AlxGa1-xN/GaN based double barrier resonant tunnelling diode (DBRTD) devices. The devices with a clear negative differential resistance (NDR) and high reproducibility are demonstrated.